ROLE OF SERUM-ASCITES ALBUMIN GRADIENT IN DIFFERENTIAL DIAGNOSIS OF ASCITES - Younas, Muhammad; Sattar, Abdus; Hashim, Rizwan; Ijaz, Aamir; Dilawar, Muhammad; Manzoor, Sayed Mohsin; Ali, Asif; Khan, Farooq Ahmad (Journal of Ayub Medical College Abbottabad, 2012)
Background: The classification of ascites as ’˜exudative’ and ’˜transudative’ based on ascitic fluid total protein (AFTP) has been challenged in many clinical conditions like cardiac ascites, patients on prolonged diuretic therapy and malignant ascites because it had poor diagnostic efficacy. These drawbacks have led to the development of another approach to classify ascites, which is based on Serum-Ascites Albumin Gradient (SAAG) to differentiate ascitic fluid into two categories: SAAG ‰¥11 g/L in ascites due to portal hypertension and SAAG <11 g/L in ascites unrelated to portal hypertension. Objective of this study was to compare the diagnostic efficacy of serum/ascites fluid albumin gradient and ascitic fluid total protein in patients having ascites. Methods: This Crosssectional comparative study was conducted in the Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, Rawalpindi from 1st Jun 2007 to 30th May 2008. Ninety-three patients were included in the study by non probability convenience sampling. The patient grouped as: (Group I) 73 cases of liver cirrhosis, (Group II) 14 cases of hepatoma and 6 cases of tuberculous ascites. Ascitic fluid specimen and 3 ml blood were obtained for ascitic fluid estimation of ascitic fluid albumin, total proteins and serum albumin. Diagnostic efficacy of SAAG and AFTP was calculated by comparing the results with clinical, ultrasonographic, histopathological findings, ascitic fluid cell count/acid fast bacilli culture and other relevant investigations. Results: Seventy-three cases had liver cirrhosis (group I), 14 cases had hepatoma and 6 cases had tubercular ascites (group II). Age ranged 25-80 years with mean age 56 years. Diagnostic accuracy, Sensitivity, Specificity, Positive predictive value (PPV) and Negative predictive value (NPV) of SAAG were 96%, 97%, 95%, 98.6%, and 90% respectively, whereas those of AFTP were 56%, 53%,70%, 86%, and 29% respectively. Conclusion: Differential diagnosis of ascites should be based on SAAG because diagnostic efficacy of SAAG was significantly higher than AFTP in work-up of ascites. Keywords: Ascites, Serum/ascites albumin gradient, Ascitic fluid total protein